Analisis Implementasi Teknik Smash Cut dalam Penguatan Unsur Dramatik pada Film Pendek Lah Kok Saya? - Mutia Khairani Zahwa; Wahyu Nova Riski (CV. ITTC INDONESIA, 2026)
The film Lah, Kok Saya? is a fictional horror-comedy that explores the misunderstandings often experienced by university students living in boarding houses. Miscommunication, differences in perception, and impulsive reactions frequently transform simple everyday situations into interpersonal conflicts, creating dramatic moments that can be effectively represented through cinematic storytelling. This project aims to implement the smash cut technique as an editing strategy to enhance dramatic elements through contrasts in visuals, audio, rhythm, and atmosphere between scenes. The application of the smash cut technique draws upon theories and concepts from Gael Chandler (smash cuts), Vsevolod Pudovkin (contrast editing), Bordwell and Thompson, Walter Murch (editing concepts), Bruce Block’s visual structure, and Lutters’ dramatic narrative elements. The creative process involved stages of preparation, design, realization, and presentation. Implementation began during pre-production with the development of the editing concept and continued during post-production through the application of smash cut transitions. Each scene employing this technique was analyzed to evaluate its contribution to dramatic storytelling. The results show that the smash cut technique was used 11 times in transitions between shots and scenes throughout the film. Its application successfully strengthened dramatic elements such as surprise, suspense, curiosity, conflict, and situational comedy by creating strong contrasts between audience expectations and the actual events presented on screen. Furthermore, the technique maintained a dynamic storytelling rhythm, accelerated narrative progression, and effectively reinforced the horror-comedy genre identity of Lah, Kok Saya?, demonstrating that smash cut functions not only as a visual transition but also as an effective narrative device for enhancing dramatic storytelling.